Title health and sanitation in Brazil: a narrative review on the association of basic sanitation conditions with waterborne diseases (Research, Society and Development, 2021)
Basic sanitation needs special attention, given its direct relationship with human health, a concern that dates back to the most ancient civilizations. In this sense, the research aims to present the relationship between basic sanitation conditions in Brazil and waterborne diseases. This is a narrative literature review study, with a qualitative approach and the hypothetical-deductive method. There is a direct relationship between waterborne diseases and basic sanitation conditions, especially in many cities in the interior of the country, especially in the North and Northeast regions of Brazil. According to the IBGE, in 2018, among cities in Brazil, the most notified waterborne disease was dengue (26.9% of the total), followed by diarrhea (23.1%) and verminosis (17.2 %). Therefore, it is up to the State not only to create public policies, but also to plan and invest in enforcing the legislation that regulates the provision of adequate access to water and sanitation services to the entire population.